2010
DOI: 10.1063/1.3499309
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics at nanoscale: Raman–Brillouin scattering from thin silicon-on-insulator layers

Abstract: The complex evolution of strain during nanoscale patterning of 60 nm thick strained silicon layer directly on insulator Appl. Phys. Lett. 94, 243113 (2009); 10.1063/1.3157134Effects of focused gallium ion-beam implantation on properties of nanochannels on silicon-on-insulator substrates J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Having been exploited for a long time for the measurement of the elastic properties of bulk materials [12][13][14] and of films, 12,[15][16][17] they are finding new applications. [18][19][20][21][22][23][24][25][26][27] The accuracy of the elastic characterization achievable by SBS was somehow puzzling since the pioneering work of Sandercock. 28 Although significant insight has been gained on the precision of spectra, 13,29 a comprehensive assessment of the whole measurement process, down to the final results in terms of elastic moduli, does not seem to have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Having been exploited for a long time for the measurement of the elastic properties of bulk materials [12][13][14] and of films, 12,[15][16][17] they are finding new applications. [18][19][20][21][22][23][24][25][26][27] The accuracy of the elastic characterization achievable by SBS was somehow puzzling since the pioneering work of Sandercock. 28 Although significant insight has been gained on the precision of spectra, 13,29 a comprehensive assessment of the whole measurement process, down to the final results in terms of elastic moduli, does not seem to have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Therefore, previous studies on ultralow-frequency Raman scattering from a top Si layer with thicknesses of 29−33 nm on a SOI wafer were focused on using visible laser excitation (413.1 nm), even though the penetration depth of the respective laser beam was almost twice the Si thickness. 28,29 In that case, the signal at ultralow frequencies was affected by the background signal from the base Si of the SOI wafer. Therefore, to avoid any further optical effects of the base Si layer on the thin Si NM, modifying the sample structures is critical.…”
mentioning
confidence: 99%
“…Brillouin spectroscopy was exploited to characterize tetrahedral amorphous carbon films of thicknesses of hundreds of nanometres (Chirita et al, 1999), tens of nanometres (Ferrari et al, 1999), down to a few nanometres (Beghi et al, 2002). It was also shown that inelastic light scattering can be sensitive to nanometric thickness differences (Lou et al, 2010). By Brillouin spectroscopy it was also possible to characterize buried layers in silicon-on-insulator structures (Ghislotti & Bottani, 1994).…”
Section: Brillouin Spectroscopymentioning
confidence: 99%